Contrast‐enhanced ultrasound features of focal pancreatic lesions in dogs. (24th August 2022) - Burti, Silvia; Zotti, Alessandro; Rubini, Giuseppe; Orlandi, Riccardo; Bargellini, Paolo; Bonsembiante, Federico; Contiero, Barbara; Banzato, Tommaso
Abstract: Background: Contrast‐enhanced ultrasound (CEUS) features of pancreatic lesions are poorly reported in veterinary literature. Methods: Qualitative and quantitative features of pancreatic benign (nodular hyperplasia [NH], cyst and abscess) and malignant (adenocarcinoma and insulinoma) lesions during B‐mode and CEUS examinations are described in 75 dogs. Results: Adenocarcinomas ( n = 23) had mixed echogenicity at B‐mode, and they were hypoenhancing or non‐enhancing at CEUS, with a non‐homogeneous and cystic enhancement pattern. Insulinomas ( n = 23) appeared as hypoechoic lesions at B‐mode, and as hyperenhancing, homogeneous and solid lesions at CEUS. NH ( n = 17) had an constant appearance, being hypoechoic at ultrasound (US) and isoenhancing at CEUS. Cysts ( n = 7) were all anechoic, with acoustic enhancement clearly detectable at US, but were non‐enhancing at CEUS. Lastly, abscesses ( n = 5) had mixed echogenicity, and they showed both hyperenhancement and non‐enhancement at CEUS. Hypoenhancement and non‐homogeneous appearance had a moderate diagnostic accuracy in the detection of adenocarcinomas. In particular, hyperenhancement was evident only in malignant lesions (adenocarcinomas and insulinomas). Conclusion: CEUS, in combination with B‐mode US features, is a valuable tool for distinction of benign and malignant abnormalities of the pancreas and can potentially differentiate insulinomas from adenocarcinomas.